(untitled) (Austrian Journal of Statistics, 2014)
Various robust versions of the classical methods of power spectra estimation are considered. Their performance evaluation is studied in autoregressive models with contamination. It is found out that the best robust estimates of power spectra are based on robust highly efficient estimates of autocovariances. Several open problems for future research are formulated.